Paracelsus (Theophrastus Bombast von Hohenheim, 1493-1541), Cosmological and Meteorological Writings - Kahn, Didier,; Weeks, Andrew, (Aries Book Series ;, 2024)
Paracelsus (1493-1541) stands at a crossroads associated with the Renaissance and Reformation. His cosmological-meteorological writings exemplify the turning point that concluded the older worldview and opened fresh avenues. His nature philosophy is inseparable from his medicine. This volume encompasses Paracelsus's writings on cosmology and meteorology in the German original with facing-page translations. The reliable source texts have been treated with methods of critical edition. The source text and translation are accompanied by commentary elucidating their obscurity through the context of his full corpus while placing them in the context of the best secondary literature from his time to the present.